Referent geometric entities in orthodontics on 3D models - Majstorović Nemanja V.; Mačužić Jelena; Glišić Branislav (Serbian Medical Society - Dental Section, Belgrade, 2014)
3D modeling is often used in orthodontics. Most commonly used software today is problem- oriented CAD system (OrthoCAD and others), as well as general CAD software for engineering modeling. Both methods require definition and use of various geometric entities to describe and monitor orthodontic status, but still there have been more than one approach to definition of geometric entities that characterize orthodontic parameters. The aim of this study was to define the referent geometric entities (RGE) on 3D models, perform their classification and provide examples of their application. For defining and monitoring orthodontic parameters the following RGE groups are used: (a) basic geometric entities (point, line, straight line, plane, curve, curved surface); (b) derived geometric entities (coordinate origin, coordinate system, coordinate plane, axis, edge, perspective); and (c) anatomical geometric entities (surfaces, points). In this study, using 11 examples is shown how orthodontic parameters can be modeled over three classification groups RGE. Presented analysis and RGE examples indicate that RGE give interdisciplinary and systematic approach to computer modeling in orthodontics, and create a basis for development and implementation of methods of anatomical features in orthodontics which can be used to set up an integrated orthodontic parameter.